Effects of different Raman pumping schemes on stimulated Brillouin scattering in a linear cavity - Shirazi, Mohammadreza Rezazadeh; Biglary, M.; Harun, Sulaiman Wadi; Thambiratnam, Kavintheran; Ahmad, Harith (Optical Society of America, 2008)
The effects of backward, forward, and bidirectional Raman pumping schemes on stimulated Brillouin scattering (SBS) is investigated in this study. By using a linear cavity, we utilize residual Brillouin pump (BP) and Raman pump (RP) power after each transmission through a 25 km single-mode fiber (SMF) used as a gain medium. The SBS threshold power is reduced in the forward, backward, and bidirectional Raman pumping schemes by 2.5, 1.75, and 2.75dB, respectively when the 1480nm RP power is fixed at 150mW and the BP wavelength is 1580 nm. Surprisingly, it is revealed that the SBS threshold reduction depends strongly and solely on Raman gain and it is independent of the Raman pumping schemes. In addition, the effect of Raman amplification on SBS is more effective at the SBS threshold, especially in the bidirectional and forward schemes.